Clinical Study on Treatment of Simple Obesity with Acupuncture - 刘志诚 孙凤岷 胡葵 黄国琪 (Journal of acupuncture and tuina science, 2004)
Better therapeutic effects have been achieved in the treatment of 112 simple obesity cases, mainly with acupuncture therapy plus auxiliary treatment of acupuncture weight loss apparatus. The results showed that the effective rate was 85% in 112 cases by one course of the treatments, 92% in 84 cases by two courses of the treatments, and 98% in 43 cases by three courses of the treatments. The therapeutic effect in combination with acupuncture apparatus was better in long courses of the treatment than in the short courses of the treatments, in male than in female, in young age than in old age, in mild case than in severe condition, in short duration than in long duration, in excessive pattern than in deficient pattern, in those without complications than in those with complications, and in those without family history than in those with family history, indicating that early treatment and prolonged treatment can enhance the therapeutic effects in weight loss by acupuncture.